Psychological Intervention Program to Control Stress in Youth Soccer Players - Olmedilla, Aurelio; Moreno-Fernández, Isabel Mª; Gómez-Espejo, Verónica; Robles-Palazón, Francisco Javier; Verdú, Isidro; Ortega, Enrique (Frontiers in Psychology, 2019)
Nowadays more attention is given to the psychological preparation of athletes. The influence on the psychological well-being of the players and their sports performance seems to be one of the keys to the current sports practice. The purpose of this study was to determine the effectiveness of a psychological intervention program for stress control in young soccer players. The sample for this study included 19 federated footballers with an average age of 16.3 years (± .99), and practice experience of 10.89 years (± 1.56). The Psychological Characteristics Questionnaire related to Sports Performance (CPRD) (Gimeno, Buceta & Pérez-Llantada, 2001) was used to assess stress factors related to sports competition. A program based on Cognitive-Conductal Therapy was implemented during 8 sessions of approximately 45 minutes each. A pre-post design and a statistical analysis with the Student's t test for paired data were used. The results indicated that the post-test scores were higher than the pre-tests footballers in "Influence of the Evaluation of Performance" and "Mental Skills" factors, which supposes a significant improvement of the stress management related to the performance evaluation, as well as the use of psychological resources and techniques. In addition, the post-test scores were also higher in the "Stress Control" factor, although in this case the differences were not statistically significant. It is concluded that a psychological training program is effective to provide resources to young footballers and help them to better manage the stress of competition.